2004
DOI: 10.1007/s00277-004-0859-6
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmatic dilatation of ascending aorta in a patient with ?-thalassemia and a pseudoxanthoma elasticum-like syndrome

Abstract: The development of a diffuse elastic tissue defect resembling pseudoxanthoma elasticum (PXE) is a recently established and frequently encountered clinical entity in beta-thalassemia. The clinical spectrum of this disorder is not yet completely understood as it is continuously being enriched with novel complications that are often serious. We present here a thalassemia intermedia patient with typical PXE manifestations and a fusiform aneurysmatic dilatation of the ascending thoracic aorta, a previously unknown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…Fragmentation of elastic fibers is also a typical hallmark of the connective tissue disorder PXE [10], which is caused by mutations in the ABCC6 gene [19,20,21,22,23,24]. This disease mainly leads to alterations in dermal, ocular and all vascular tissues, and, in some cases, aneurysmatic dilatations were observed [41, 42]. In order to determine if the occurrence of sequence variations in the ABCC6 gene is associated with the presence of AAAs and to compare the frequencies of ABCC6 polymorphisms and mutations in AAA and PXE patients, we screened the ABCC6 exons 16–18, 24 and 28–30 from 133 unrelated patients with AAA, 54 PXE patients and 23 PXE relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Fragmentation of elastic fibers is also a typical hallmark of the connective tissue disorder PXE [10], which is caused by mutations in the ABCC6 gene [19,20,21,22,23,24]. This disease mainly leads to alterations in dermal, ocular and all vascular tissues, and, in some cases, aneurysmatic dilatations were observed [41, 42]. In order to determine if the occurrence of sequence variations in the ABCC6 gene is associated with the presence of AAAs and to compare the frequencies of ABCC6 polymorphisms and mutations in AAA and PXE patients, we screened the ABCC6 exons 16–18, 24 and 28–30 from 133 unrelated patients with AAA, 54 PXE patients and 23 PXE relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Because PXE-like mineralization in ␤-thalassemia patients arise independently of ABCC6 mutations 16 and is clinically and structurally identical to inherited PXE, [17][18][19][20] the calcification of elastic fibers is very likely a phenocopy of inherited PXE. Therefore, we hypothesized that a converging molecular mechanism independent of genetic mutations alters the expression of ABCC6 or disrupts the biologic properties of its product in the liver and/or kidneys as a secondary consequence of the hemoglobinopathy.…”
Section: 15mentioning
confidence: 99%
“…24 In fact, it has been shown that 85% of patients Ͼ30 years of age who have thalassemia intermedia have at least 1 of the typical manifestations of the defect, namely, skin lesions, ocular angioid streaks, and arterial degeneration, 25 whereas subclinical pathology findings were found in 96% of young patients with thalassemia major and other hemolytic conditions. 26 This defect has been related to a number of vascular and other complications, 27,28 including pulmonary arterial lesions, hence providing a structural component to the aforementioned hemolysis-related vasculopathy. 22 A hypercoagulable state is another notable finding in hemoglobinopathies.…”
Section: Pathophysiologymentioning
confidence: 99%